Recontextualising issues in the 'NISTCOL" environmental education curriculum module for Primary Diploma by Distance Learning in Zambia - Moose, John (Rhodes University, Faculty of Education, Department of Education, 2009)
This study investigated the recontextualising of the NISTCOL environmental education curriculum module for the Primary Teachers' Diploma by Distance Learning (PTDDL) in Zambia. It focused on three case sites, the NISTCOL EE curriculum module for PTDDL and the University of Zambia, the National In-Service Teacher's College (NISTCOL) and four basic schools: chalimbana, Bimbe, Chongwe and Silver Rest. The study looked at teacher professional development in environmental education in Zambia. The aims and goals were to investigate the NISTCOL EE curriculum and identifying issues that were associated with lecturers in the recontextualising process and further examine what issues were associated with curriculum recontextualisation in Zambian schools. For the conceptual constructs, the research drew on Bernstein's (1990) framework of pedagogic discourse, it traced how the pedagogic discourse was de-located from the field of production and re-located into the pedagogic practice of each stated case above. It further examined the continuities, discontinuities and changes in the official environmental discourse as it was recontextualised. The study particularly focused on Bernstein's conceptual constructs of selective appropriation and ideological transformation. In each case the Bernstein framework is used to analyze the process to identify recontextualising issues influencing pedagogical practice in the Zambian schools and college. The study revealed that each case under focus was unique but through examining the environmental discourse and pedagogical discourse in each case recontextalising issues were identified. Each case was influenced by different factors, such as lack of policy synergy, lack of EE vision at national level in Zambia, experience and knowledge, ideologies and emphasis, and depth of engagement. These factors provided me with a deeper insight into the curriculum recontextualising processes in Zambian schools.
Keywords: Environmental education -- Zambia